Prevalence of mutations associated with resistance to macrolides and fluoroquinolones in Mycoplasma genitalium: a systematic review and meta-analysis. Issue 11 (November 2020) - Machalek, Dorothy A; Tao, Yusha; Shilling, Hannah; Jensen, Jørgen S; Unemo, Magnus; Murray, Gerald; Chow, Eric P F; Low, Nicola; Garland, Suzanne M; Vodstrcil, Lenka A; Fairley, Christopher K; Hocking, Jane S; et al.
Summary: Background: Mycoplasma genitalium is now recognised as an important bacterial sexually transmitted infection. We summarised data from studies of mutations associated with macrolide and fluoroquinolone resistance in M genitalium to establish the prevalence of resistance. We also investigated temporal trends in resistance and aimed to establish the association between resistance and geographical location. Methods: In this systematic review and meta-analysis, we searched PubMed, Embase, and MEDLINE for studies that included data for the prevalence of mutations associated with macrolide and fluoroquinolone resistance in M genitalium published in any language up to Jan 7, 2019. We defined prevalence as the proportion of M genitalium samples positive for key mutations associated with azithromycin resistance (23S rRNA gene, position 2058 or 2059) or moxifloxacin resistance (S83R, S83I, D87N, or D87Y in parC ), or both, among all M genitalium samples that were successfully characterised. We used random-effects meta-analyses to calculate summary estimates of prevalence. Subgroup and meta-regression analyses by WHO region and time period were done. This study was registered with PROSPERO, number CRD42016050370. Results: Overall, 59 studies from 21 countries met the inclusion criteria for our study: 57 studies of macrolide resistance (8966 samples), 25 of fluoroquinolone resistance (4003 samples), and 22 of dual resistance to macrolides and fluoroquinolones (3280 samples). The summary prevalence of mutations associated with macrolide resistance among M genitalium samples was 35·5% (95% CI 28·8–42·5); prevalence increased from 10·0% (95% CI 2·6–20·1%) before 2010, to 51·4% (40·3–62·4%) in 2016–17 (p<0·0001). Prevalence of mutations associated with macrolide resistance was significantly greater in samples in the WHO Western Pacific and Americas regions than in those from the WHO European region. The overall prevalence of mutations associated with fluoroquinolone resistance in M genitalium samples was 7·7% (95% CI 4·5–11·4%). Prevalence did not change significantly over time, but was significantly higher in the Western Pacific region than in the European region. Overall, the prevalence of both mutations associated with macrolide resistance and those associated with fluoroquinolone resistance among M genitalium samples was 2·8% (1·3–4·7%). The prevalence of dual resistance did not change significantly over time, and did not vary significantly by geographical region. Interpretation: Global surveillance and measures to optimise the efficacy of treatments—including resistance-guided strategies, new antimicrobials, and antimicrobial combination approaches—are urgently needed to ensure cure in a high proportion of M genitalium infections and to prevent further spread of resistant strains. Funding: Australian National Health and Medical Research Council.